Assessment of the influence of Concrete Modification in the Water Uptake/Evaporation Kinetics by Electrochemical Impedance Spectroscopy. (1st September 2017) - Vicente, C.; Castela, A.S.; Neves, R.; Montemor, M.F.
Abstract: Corrosion of reinforcing steel in concrete is a worldwide problem. An important factor affecting such process is the concrete composition and, especially the presence of additives. In fact, the kinetics of water absorption and water evaporation are affected both by the environment conditions and by the nature of the additives. This is important for powdered additives, which can partially occlude the porous structure, changing porosity and permeability of concrete too. Reinforced concrete samples were modified by adding spent fluid cracking catalyst powders (SFCC) and an environment friendly commercial inhibitor. The samples were submitted to consecutive cycles of 15 day of immersion (in saturated NaCl electrolyte) followed by 15 day of drying. Samples were regularly monitored by electrochemical Impedance Spectroscopy (EIS). The results revealed that the additives interfere with the water adsorption/evaporation kinetics in concrete, a process resulting from the joint effect of diffusion and capillary processes. These interferences occur due to three combined mechanisms: two related to pore blocking and pozzolanic activity, which are the result of structural changes in concrete and affect the diffusion processes/mechanism; the third one is the capillary mechanism, which is strongly dependent from the chemical nature of the additives, but can also be influenced by structure modifications. This mechanism can increase, reduce or eliminate the capillary processes.